(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Housing construction is a key sector influencing socio-economic development, urbanization, and living standards in Uzbekistan. In recent years, the country has implemented market reforms aimed at increasing housing supply, improving affordability, and attracting investment into the construction sector. This thesis analyzes the efficiency of housing construction development with a focus on institutional and financial factors. The results show that sustainable development depends on coordination between state regulation, mortgage financing, and private investment, while challenges such as regional disparities and affordability constraints still remain.